2022
DOI: 10.1186/s12906-022-03653-7
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Mentha arvensis administration provides neuroprotection against transient global cerebral ischemia in gerbils and SH-SY5Y cells via downregulation of the MAPK signaling pathway

Abstract: Background Globally, ischemic stroke is a major health threat to humans that causes lifelong disability and death. Mentha arvensis (MA) has been used in traditional medicine to alleviate oxidative stress and inflammation-related disorders. In the present study, the neuroprotective properties of fermented MA (FMA) extract were investigated in the gerbil and SH-SY5Y cells. model of transient global cerebral ischemia. Methods Bilateral common carotid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…acidophilus showed an increase in the concentration of rosmarinic acid that could suppress MDA, NO, and corticosterone; improve body weight; decrease daily food intake and duodenum histology; and increase serotonin and β-endorphin levels in immobilization-induced stressed rats [ 12 ]. In another study, such fermented M. arvensis extract administration also provided neuroprotection against transient global cerebral ischemia in gerbils and SH-SH5Y cells by downregulating MAPK signaling [ 13 ]. In addition, M. piperita fermented with Bacillus subtilis suppressed PMA-induced ROS, ERK, and MUC5AC mRNA protein expression in lung epithelial cells [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…acidophilus showed an increase in the concentration of rosmarinic acid that could suppress MDA, NO, and corticosterone; improve body weight; decrease daily food intake and duodenum histology; and increase serotonin and β-endorphin levels in immobilization-induced stressed rats [ 12 ]. In another study, such fermented M. arvensis extract administration also provided neuroprotection against transient global cerebral ischemia in gerbils and SH-SH5Y cells by downregulating MAPK signaling [ 13 ]. In addition, M. piperita fermented with Bacillus subtilis suppressed PMA-induced ROS, ERK, and MUC5AC mRNA protein expression in lung epithelial cells [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such fermented extracts could suppress MDA, NO, and corticosterone; improve body weight; decrease daily food intake and duodenum histology; and increase serotonin and βendorphin levels in immobilization-induced stressed rats [24]. In another study, such fermented M. arvensis extract administration also provided neuroprotection against transient global cerebral ischemia in gerbils and SH-SH5Y cells by downregulating MAPK signaling [25]. In addition, M. piperita fermented with Bacillus subtilis suppressed PMA-induced ROS, ERK, and MUC5AC mRNA protein expression in lung epithelial cells [26].…”
Section: Discussionmentioning
confidence: 91%
“…Transient cerebral ischemia in gerbils is brought on by blocking both common carotid arteries for 5 min [ 46 , 47 , 48 ]. In our previous study, severe neuronal cell damage was identified 5 days after induction of ischemic insult [ 36 , 49 ]. We also found neuronal cell death and activation of microglial cells and astrocytes in the most vulnerable part of the brain (hippocampus) after 5 days of TI.…”
Section: Discussionmentioning
confidence: 99%
“…We implemented a technique to induce TI in gerbils that was described previously [ 35 , 36 ]. In brief, inhalation anesthesia was implemented with a combination of nitrous oxide, oxygen, and isoflurane (68%, 32%, and 2.5%, respectively).…”
Section: Methodsmentioning
confidence: 99%